Interaction model between sea lampreys and ecosystem based on Logistics model - Yue, Zhu; Lang, Xia (Transactions on Environment, Energy and Earth Sciences, 2024)
An interaction model between lampreys and ecosystem based on logistic equation is established. By solving the differential equations, the sex ratio of lampreys varies with the number of other populations, the number of its own population and the growth rate. The results suggest that changes in the sex ratio will give lampreys an advantage in population competition and inhibit the development of other populations.Logistics equations to study the performance of lampreys in population competition, and environmental equations to discuss lampreys management plans. This has practical implications for dealing with invasive species in the Great Lakes and elsewhere. In addition, we studied and built models to explore the pros and cons of species being able to change their sex ratios in response to resource availability and gain insight into the resulting ecosystem interactions.